2007
DOI: 10.1002/jcc.20720
|View full text |Cite
|
Sign up to set email alerts
|

Can a physics‐based, all‐atom potential find a protein's native structure among misfolded structures? I. Large scale AMBER benchmarking

Abstract: Recent work has shown that physics-based, all-atom energy functions (AMBER, CHARMM, OPLS-AA) and local minimization, when used in scoring, are able to discriminate among native and decoy structures. Yet, there have been only few instances reported of the successful use of physics based potentials in the actual refinement of protein models from a starting conformation to one that ends in structures, which are closer to the native state. An energy function that has a global minimum energy in the protein's native… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(84 citation statements)
references
References 45 publications
5
79
0
Order By: Relevance
“…We performed numerous analyses to establish the significance of our refinement results. One of the common problems in the training of potential functions is the decoy generation procedure (20). Some decoy sets contain certain characteristics that are easy to memorize during training, but are not transferable to other decoy sets.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We performed numerous analyses to establish the significance of our refinement results. One of the common problems in the training of potential functions is the decoy generation procedure (20). Some decoy sets contain certain characteristics that are easy to memorize during training, but are not transferable to other decoy sets.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the energy surface should be funnel-like so that the potential can drive the structure toward lower energy, more native-like conformations. For this to occur, the energy function must have a correlation with native structure similarity (20). Previously (21), we explored the possibility of creating a funnel-like shape for the Amber ff03-based potential (22) by global optimization of the weights of the individual energy components.…”
mentioning
confidence: 99%
“…The result of our study of sampling loop conformations to an RMSD of 1.57 Å and yet their detection is inferior by a resolution of $ 1 Å , indicates the need for improvements in the energy function. Other reported studies have clearly shown that the native minimum on an all-atom potential energy function often does not appear to be the lowest free-energy state (see, e.g., Wroblewska and Skolnick 35 ). This difficulty originates from imperfections in the underlying force field plus GB implicit solvent models.…”
Section: Computational Cost and Overall Assessmentmentioning
confidence: 97%
“…It has recently been shown that MD does not help discriminate the native state from its decoys, in that the correlation between energy and rmsd vanishes after MD simulation with AMBER and a GB potential (45). Other recent work used replica exchange sampling with CHARMM22/GBSW potential to refine homology modeling targets with spatial restraints; it worked well but it is unclear whether this would have happened without the restraints (20).…”
Section: Molecular Dynamics In Explicit Solventmentioning
confidence: 99%